Relative efficacy of psychological interventions following interpersonal trauma on anxiety, depression, substance use, and PTSD symptoms in young people: A meta‐analysis. Issue 11 (1st February 2022) - Peters, Wilma; Rice, Simon; Alvarez‐Jimenez, Mario; Hetrick, Sarah E.; Halpin, Emma; Kamitsis, Ilias; Santesteban‐Echarri, Olga; Bendall, Sarah
Abstract: Aim: Interpersonal trauma exposures are associated with anxiety, depression, and substance use in youth populations (aged 12–25 years). This meta‐analysis reports on the efficacy of psychological interventions on these symptom domains in addition to post‐traumatic stress. Methods: Following PRISMA guidelines, a search of electronic databases was performed for randomized controlled trials (RCTs) assessing interventions for young people following interpersonal trauma exposure. Risk of bias was assessed using the Cochrane Risk of Bias tool. Data were analysed using random‐effects meta‐analyses. Results: Of the 4832 records screened, 78 studies were reviewed, and 10 RCTs, involving 679 participants (mean age 15.6 years), were analysed. There was a large pooled effect size for post‐traumatic stress (7 studies, g = 1.43, 95% CI [0.37, 2.15], p = .002) and substance use (2 studies, g = 0.70, 95% CI [−0.11, 1.22], p < .001) and small effect sizes for anxiety (4 studies, g = 0.30, 95% CI [0.10, 0.49], p = .003), and trend‐level effect for depression (10 studies, g = 0.27, 95% CI [0.00, 0.54], p = .052). Heterogeneity was significant for post‐traumatic stress and moderate for depression. Conclusions: High‐quality RCTs of psychological interventions for anxiety, depression, substance use, and post‐traumatic stress symptoms in young people exposed to interpersonal trauma are scarce. While available studies show either statistically significant or trend‐level efficacy for psychological interventions in reducing these symptoms, wide confidence intervals, heterogeneity and small sample size mean that results need to be interpreted with caution.